2013
DOI: 10.1159/000353893
|View full text |Cite
|
Sign up to set email alerts
|

Increased Activation and Differentiated Localization of Native and Phosphorylated STAT3 in Nasal Polyps

Abstract: Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a multifactorial disease; the underlying mechanisms of cell signalling are not fully understood. STAT3 (signal transducer and activator of transcription 3) is a phosphokinase and a key signalling molecule implicated in cell cycle regulation. We studied the distribution and expression of STAT3 to examine the role of STAT3 in the pathogenesis of CRSwNP. Methods: We investigated tissue samples of the nasal polyps and inferior turbinate of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
1
3
1
Order By: Relevance
“…STAT proteins are critical mediators of cytokine signaling among which STAT3 has been identified to be linked to tumorigenesis and inflammation (12, 3638). Previous studies proposed that STAT3 and its phosphorylated form, P-STAT3, were mainly located in the superficial layer of the epithelium of CRSwNP patients, while hardly expressed in normal tissues (39, 40), similar to the expressions of IL-19 and MUC5AC observed in the present study. We wonder if the effect of STAT3 in IL-19, induced MUC5AC production.…”
Section: Discussionsupporting
confidence: 89%
“…STAT proteins are critical mediators of cytokine signaling among which STAT3 has been identified to be linked to tumorigenesis and inflammation (12, 3638). Previous studies proposed that STAT3 and its phosphorylated form, P-STAT3, were mainly located in the superficial layer of the epithelium of CRSwNP patients, while hardly expressed in normal tissues (39, 40), similar to the expressions of IL-19 and MUC5AC observed in the present study. We wonder if the effect of STAT3 in IL-19, induced MUC5AC production.…”
Section: Discussionsupporting
confidence: 89%
“…17 The results of this study are in accordance with the results of our own research concerning STAT3. 18 In contrast to our study, Wang et al 17 detected decreased levels of pSTAT5 compared with controls. However, Wang et al 17 examined polyps from Asian patients, and we examined polyps from Caucasian patients.…”
Section: Discussioncontrasting
confidence: 99%
“…STAT1 is activated in nasal polyps compared with healthy nasal tissue, and its activation may be related to abnormalities in NO metabolism in CRSwNP. 14 STAT3 was found to be activated in four studies 1518 and was described as downregulated in one report. 19 Corticosteroid treatment of patients with CRSwNP leads to decreased phosphorylated STAT3 (pSTAT3).…”
mentioning
confidence: 99%
“…A previous study indicated that IL-6 signaling may play a pathogenic role in CRSwNP [35]. In addition, p-STAT3 was found in both the superficial and basal layer of the epithelium of the polyps, which plays a crucial role in the proliferative development of nasal polyps [36]. Moreover, Lai et al in 2019 indicated that IL-19 may upregulate mucin production via the STAT3 pathway in CRS [37].…”
Section: Discussionmentioning
confidence: 97%